Bacteriological Assessment of Air Quality in Male and Female Hostels At Federal University Dutsin-Ma, Katsina State (Sahel Journal of Life Sciences FUDMA, 2023)
The evaluation of microorganisms present in indoors has become necessary, as how safe the air in our surrounding environment where we spent time is fundamental to our wellbeing. Hence, this study was aimed at assessing the indoor air quality of Male and Female hostel in Federal University Dutsin-Ma, Katsina State. Using the settle plate sampling technique using open Petri dishes containing culture with sampling done twice daily morning and eveningÂ  consecutively. The microbial isolates were characterized and identified based on macroscopic, microscopic and biochemical characteristics. Total aerobic bacterial isolated ranged between the average of 40cfu/m3 - 164cfu/m3& 20cfu/m3 â€“ 182cfu/m3for male and female respectively. The predominant bacterial species isolated and characterized from all sample were Staphylococcus spp, Micrococcus spp and Bacillus spp. Staphylococcus sp having the highest percentage of 57.7%, followed by Bacillus spp with 32.78% and Micrococcus spp having the least with 9.83%. The result of this studies shows that the organisms isolated which are Staphylococcus spp, Micrococcus spp and Bacillus spp. May be the potential cause of several infections to the students living in the hostels which may be due to overcrowding, limited indoor air and higher activities of the occupants.